Development of Guidebook for Rational Emotive Behavior Counseling to Improve Vocational High School Students’ Career Self-Efficacy - Khasanah, Imro’atul; Hotifah, Yuliati; Rachmawati, Indriyana; Da Costa, Augusto (citeus, 2025)
Career decision-making of vocational high school students is still something that does not receive serious attention and causes students to experience career decision difficulties. One of the causes of difficulty in making career decisions is students' lack of confidence in their abilities. This study aims to develop a guidebook for rational emotive behavior counseling (REBC) which is intended for school counselors. REBC counseling can help counselees to understand their cognitive conditions that lead to emotional disturbances so that counselees can change irrational thoughts and understand the consequences of their behavior. The guidebook that was developed contains material on career self-efficacy, REBC counseling, and procedures for implementing REBC counseling in six stages of counseling sessions. This development research uses research and development methods from Borg and Gall with research procedures that have been adapted to the conditions of the research field. The guidebook validity test was carried out by one expert who tested the material, one media expert, and two school counselors as potential users by taking into account the accuracy assessment, usability assessment, convenience assessment, and attractiveness assessment. The results of the material and media expert test were analyzed using the average, while the results of the prospective user test were analyzed using the inter-rater agreement. The test results show that the guidebook gets a high score and it can be concluded that the REBC counseling guide that has been developed is suitable for use by school counselors in implementing REBC in order to increase the career self-efficacy of vocational high school students.